2011
DOI: 10.1017/s0142716411000427
|View full text |Cite
|
Sign up to set email alerts
|

Deeper than shallow: Evidence for structure-based parsing biases in second-language sentence processing

Abstract: This study examines the reading patterns of native speakers (NSs) and high-level (Chinese) nonnative speakers (NNSs) on three English sentence types involving temporarily ambiguous structural configurations. The reading patterns on each sentence type indicate that both NSs and NNSs were biased toward specific structural interpretations. These results are interpreted as evidence that both first-language and second-language (L2) sentence comprehension is guided (at least in part) by structure-based parsing strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
53
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 70 publications
(136 reference statements)
9
53
0
Order By: Relevance
“…Turning to later time windows which might exhibit N400 effects in filler‐gap which sentences, there were no significant differences in the 450–700 ms window. Several studies have shown that L2 learners read more slowly than native speakers, and sometimes show delayed effects (e.g., Dussias & Pinar, ; Williams, ; Witzel, Witzel, & Nicol, ). For this reason, we wondered whether the L2 group would show plausibility effects for the filler‐gap sentences in an even later time window, 700–900 ms after the onset of the critical word (note that this time window extends into the next word of the sentence).…”
Section: Resultsmentioning
confidence: 99%
“…Turning to later time windows which might exhibit N400 effects in filler‐gap which sentences, there were no significant differences in the 450–700 ms window. Several studies have shown that L2 learners read more slowly than native speakers, and sometimes show delayed effects (e.g., Dussias & Pinar, ; Williams, ; Witzel, Witzel, & Nicol, ). For this reason, we wondered whether the L2 group would show plausibility effects for the filler‐gap sentences in an even later time window, 700–900 ms after the onset of the critical word (note that this time window extends into the next word of the sentence).…”
Section: Resultsmentioning
confidence: 99%
“…Because L2 acquisition involves more than simply memorizing individual sounds, words, or verbal paradigms, there is an ongoing debate about the causes underlying the observed incomplete acquisition. Some scholars assert that the relevant L2 information—including even subtle aspects of the L2 grammar—can be fully acquired by adult learners (e.g., Schwartz & Sprouse 1994, 1996; Lardiere 1998a,b; Prévost & White 2000; Bruhn de Garavito & White 2002; Keating 2009; Gillon Dowens et al 2010; Alarcón 2011; Foucart & Frenck-Mestre 2011, 2012; Grüter et al 2012; Witzel et al 2012; Hopp 2013) and challenge the existence of fundamental differences (Clahsen& Felser 2006) between native and nonnative speakers. According to this view, errors in L2 performance are modulated by a number of variables, including proficiency and immersion experience in the L2 (e.g., Kotz 2009, Pliatsikas & Marinis 2013), speed of lexical access (Hopp 2013), and availability of cognitive and computational resources (e.g., McDonald 2006, Hopp 2010).…”
Section: Dynamic Changes During Syntactic Processingmentioning
confidence: 99%
“…L2 speakers have shown sensitivity to various types of (morpho-) syntactic disambiguation cues, such as finite verbs lacking a subject (e.g., Juffs, 1998;Rah & Adone, 2010;Roberts & Felser, 2011), overt complementizers (e.g., Dussias & Cramer Scaltz, 2008), number and gender agreement (e.g., Jackson & Roberts, 2010;Papadopoulou & Clahsen, 2003), THE QUARTERLY JOURNAL OF EXPERIMENTAL PSYCHOLOGY, 2015 3 NATIVE/NON-NATIVE GARDEN-PATH RECOVERY or case marking (e.g., Hopp, 2006Hopp, , 2013Jackson, 2008). L2 speakers have also demonstrated sensitivity to semantic disambiguation cues (Pan & Felser, 2011) and to disambiguating punctuation marks as in (2b) above (Hopp, 2013;Witzel et al, 2012).…”
Section: Garden-path Recovery In Non-native Sentence Comprehensionmentioning
confidence: 99%